Kegagalan Outcome dalam Pengadaan Barang dan Jasa Pemerintah: Analisis Literatur atas Kesenjangan Implementasi Pengadaan Pemerintah Daerah - Muhammad Adrian Perdana; Robi Armilus (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Public procurement is a vital instrument for supporting development and public services. However, in practice, there is often a mismatch between the physical output produced and the actual outcome or impact felt by the community. This article aims to examine outcome failure in government procurement through a literature review approach, using the theoretical framework of organizational decision-making and the Input–Throughput–Output–Outcome (ITOO) model. The study finds that failures often originate from the early stages of decision-making, particularly in the phases of need identification (intelligence) and solution design. Case studies such as the Riau Main Stadium and Cik Puan Market in Pekanbaru illustrate how planning that is not based on real needs and lacks operational continuity results in abandoned infrastructure with minimal public benefit. This research recommends restructuring the procurement planning process to be more data-driven, participatory, and outcome-oriented.